If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1 = -25 Reorder the terms: -1 + 2x = -25 Solving -1 + 2x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = -25 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = -25 + 1 2x = -25 + 1 Combine like terms: -25 + 1 = -24 2x = -24 Divide each side by '2'. x = -12 Simplifying x = -12
| 6+10m=-24 | | -40n^8+32n^7+40n^5=0 | | 6(y+4)=-5(3y-2)+9y | | -24n^5-9n^3-15n-15=0 | | (x^2+1)+(-4x^2+5)= | | 10x^2+7x-5=4x^2 | | 2m+7=m+1 | | 6+3v+3-12=v-3 | | (3x-9)(2x+8)(x+4)=0 | | 72x^5-27x^3+27x+63=0 | | (x-4x^2+7)-(5x^2+5x-3)= | | r+9=3r+5-6 | | 2(-3)+3y=9 | | 3x+3x+2y=100 | | -5x+1=x-5-4x | | x(2x+5)=42 | | 6x+2y=100 | | 1-2x=2x+6-5+8 | | (m+3m^3-4m^5)+(2m^3+5m^5-4)= | | -2(4v-3)+4v=6+2(6v-9) | | 29+.08k=46.12 | | 5x-2x=5+2x | | 9p^2-16=0 | | -45-12= | | 10+5y-2y+2-7y=37+y | | x^2=8x-12 | | 4-(70-7*3)= | | 2(0)+3y=9 | | (-3+4n^2)-(5-2n^3)= | | -4n+4=-5n+2 | | 3x^2+40x+20=10x-28 | | 7Z+16=8Z-6 |